Pengaruh Faktor Internal dan Eksternal terhadap Minat Petani dalam Budidaya Bawang Putih (Allium sativum L.) - Sri Ayu Andayani; Sri Umyati; Agus Yadi Ismail; Miftah Dieni Sukmasari; Acep Atma Wijaya; Siti Shofiyatun Zakiyah; Dadan Ramdani Nugraha (Universitas Galuh, 2026)
Garlic is a strategic horticultural commodity whose national needs are still highly dependent on imports. Therefore, developing domestic production requires strong farmer support and interest. This study aims to: (1) describe the characteristics and level of farmer interest in garlic cultivation; and (2) analyze the relationship between internal and external factors and farmer interest. The study was conducted in Nunuk Village, Maja District, Majalengka Regency, using a quantitative descriptive approach. The sample was determined through a census of 20 garlic farmers. Data were collected through questionnaires, interviews, and observations, then analyzed using descriptive percentage analysis, scoring, and Spearman's Rank correlation test at a 5% significance level. The results showed that the majority of farmers had a very high level of interest (70%), with internal and external factors in the moderate category. The correlation test showed that among the six indicators tested, only the availability of cultivation technology and information was significantly related to farmer interest (ρ = 0.484; p = 0.030), while the other indicators did not show a significant relationship. These findings confirm that strengthening access to cultivation technology and information is key to fostering farmer interest in supporting the garlic self-sufficiency program.